Ngabulâ Vis-À-Vis Modernity: Tabarruk Practice in Bangkalan Pesantren - Djakfar, Fera Andriani; Permatasari, Puspita Ayu (Institut Agama Islam Negeri Madura, 2020)
Ngabulâ is a tradition practiced by some santris in Bangkalan pesantrens in order to seek blessings (tabarruk) by serving the kiai. Those santris are called kabulâ or khaddam. In fact, ngabulâ is very important for kiai’s life and also the pesantren in Bangkalan, but unfortunately the study of it is still rarely done. Therefore, this research aims to explore several things: the meaning of ngabulâ in Bangkalan pesantren according to the actors and the dynamic of ngabulâ in Bangkalan pesantren based on the continuity and change theory conceptualized by John Obert Voll. This research was conducted in some pesantrens in Bangkalan from early 2019 to mid-2020, and the data was collected through interviews, observation, and documentation. This research used the paradigm of social definition by applying phenomenology. The theory used is continuity and change conceptualized by John Obert Voll in observing the resurgence of Islam in the modern world. This research concludes some facts: first, this study finds that ngabulâ for the actors involved in it (the kabulâ , kiai and their families, and the kabulâ ’s parents) means respect, dedication, learning media, and a source of blessings. Second, there is continuity and change in the ngabulâ, especially in the motives, goals, and forms of ngabulâ. To observe the continuity and change of it, the researcher uses the basic styles of action conceptualized by Voll with modification and addition, namely: adaptation, authority of the text, conservative actions, and charisma. In addition to this research, the researcher added one thing, i.e. generous manner of the kiai.